Studi Kasus: Penerapan Lean Six Sigma Dengan Pendekatan DMAIC Dalam Menurunkan Waste Defect Pada Lini Perakitan Kendaraan Roda Empat - Setiawan Setiawan; Algi Fahri; Choesnul Jaqin (Universitas Mercu Buana, 2019)
Indonesia is one of the four-wheeled vehicle manufacturers in ASEAN and is a country that is developing dramatically in the automotive sector. The ongoing challenge faced as a manufacturer of four-wheeled vehicles now is how the industry continues to improve quality and reduce waste activities in the production process in order to have a strong competitiveness in the era of increasingly fierce competition today. Lean Six Sigma is a systematic data-driven methodology that integrates two powerful business improvement strategies to improve product quality and reduce waste. In this context, this study uses the Lean Six Sigma framework with the DMAIC methodology approach with the aim of improving the quality of the process and reducing waste of defect products along the four-wheeled vehicle assembly line.. The industrial case study was carried out in one of the four-wheeled vehicle manufacturers in the GIIC Indonesia industrial area. It begins with identifying the waste that occurs with values stream mapping and taking defect data for 20 working days during October 2020. In its implementation, it has succeeded in reducing the defect of product from 4,556 DPMO to 2,047 or increasing the sigma level of the company from 4.10 to 4.38.